DYNAMIC URBAN INTELLIGENCE: A COMPREHENSIVE ANALYSIS OF THE EVOLUTIONARY TRAJECTORY OF SMART CITIES AND TRANSPORTATION SYSTEMS - Muhammad Younus; Achmad Nurmandi; Nisaul Hasanah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This study aims to analyze the characteristics of smart cities and smart transportation trends in the last ten years. The development of technology and the increasing level of mobility have created a concept of a smart city as an effort to embody an effective and efficient sustainable life, including in the transportation sector. The Smart City concept is an effort to integrate information and communication in city management, while smart transportation is one of the essential components of implementing a smart city that combines information and communication technology with the transportation sector. The adaptation of the two creates a system known as the Intelligent Transportation System (ITS). This research used a bibliometric analysis to analyze data from the last ten years using the Scopus database and CiteSpace software. The number of publications on smart cities and smart transportation trends has increased overall in the last ten years, with China having the highest number. A bibliometric analysis found that the trend consists of 15 significant clusters: smart transportation applications business model, geomatics, big data, enabling technologies security, cloud computing, cyber-physical system, traffic congestion level, city buses, comprehensive performance analysis, energy-aware intrusion detection model, privacy-preserving authentication protocol, communication-oriented perspective, intelligent transportation system, numerical calibration method, and cyber-physical system. The study also considers both macro and micro perspectives. It should evaluate how urban intelligence influences resource allocation, sustainability goals, and equitable access to services while also focusing on transportation systems, autonomous vehicles, and last-mile connectivity.